1996
DOI: 10.1246/bcsj.69.2801
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Effects on Intramolecular Exciplex Fluorescence of Chain-Linked Phenanthrene and N,N-Dimethylaniline: Influence of Chain Length, Solvent, and Temperature

Abstract: Magnetic field effects (MFEs) on the intramolecular exciplex fluorescence of a chain-linked phenanthrene (Phen)/N,N-dimethylaniline (DMA) system, Phen–(CH2)n–O–(CH2)2–DMA, have been studied in the magnetic fields (≤0.62 T) as functions of (1) solvent polarity (ε = 7.6—36.7), (2) chain length (n = 4—12), and (3) temperature (223—333 K). The MFEs on the exciplex fluorescence are attributable to the singlet–triplet intersystem crossing in the intramolecular radical ion pair which is in dynamic equilibrium with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…The observation of the MFE in exciplex fluorescence in both the chain-linked phenanthrenedimethylaniline dyad and the supramolecular complex of zinc(II)-tetraphenylporphyrin with viologen, described by Japanese researchers [39], was also assigned to the fast equilibrium between RIP and exciplex.…”
Section: Resultsmentioning
confidence: 86%
“…The observation of the MFE in exciplex fluorescence in both the chain-linked phenanthrenedimethylaniline dyad and the supramolecular complex of zinc(II)-tetraphenylporphyrin with viologen, described by Japanese researchers [39], was also assigned to the fast equilibrium between RIP and exciplex.…”
Section: Resultsmentioning
confidence: 86%
“…The authors suggested that the presence of the radical cation in nonpolar solvents is due to fast, comparable with lifetime of RIP, transitions between solvent separated and contact RIP (exciplex). The observation of MFE on exciplex fluorescence in chain linked phenanthrene-dimethylaniline dyad and in supramolecular complex of zinc(II)-tetraphenylporphyrin with viologen, which was described by Japanese researchers [33], was also explained by the existence of fast equilibrium between RIP and exciplex.…”
Section: Nmr (Top) and Tr Cidnp At 1µs Delay (Bottom) Spectra Detecmentioning
confidence: 83%
“…[51] Furthermore, it has been shown that phenanthrene efficiently forms exciplexes with aromatic amines, in particular with N,N-dimethylaniline. [52] Given that exciplex emission normally occurs at wavelengths higher than that of the emission of the isolated constituents, we assume again that no exciplex is formed in the 3phenH/3phenNH 2 duplex, although we cannot completely rule it out. The mechanistically mostplausible explanation for the observed fluorescence behavior therefore involves charge transfer.…”
Section: Wwwchemeurjorgmentioning
confidence: 97%